PENGARUH WAKTU FERMENTASI DAN KOMPOSISI LIMBAH KULIT BUAH AREN (Arenga pinnata) DENGAN STARTER KOTORAN SAPI TERHADAP BIOGAS YANG DIHASILKAN - Deril Clinton; Netti Herlina (Universitas Sumatera Utara, 2015)
Sugar palm or commonly called as Aren (Arenga pinnata) is a multipurpose crop. The widely use of sugar palm for food industries, generates sugar palm leather waste which can be used as a biomass for biogas production. This study aims to determine the quality and the quantity of biogas made from a mixed of sugar palm leather waste and water using batch anaerobic digester system and to evaluate the economic potential of biogas production from the mixture. Research carried out by mixing sugar palm leather with water in a ratio of 1:13; 1:11,5; 1:10; 1:9; and 1:8 (w/w) with cow dung as a starter mixed with water in an anaerobic digester batch system. Observed variables are biogas, biogas composition, Total Suspended Solid (TSS) and Chemical Oxygen Demand (COD) and analyzed fermentation slurry for every 3 days. pH for this study is set in the range of 6,4-8. The largest volume of biogas production is found at a ratio 1:11,5 (w/w) mixture of sugar palm leather and water that is 637 mL for total waste 1,5 L with 60,983 % methane contain. TSS removal percentage obtained was 88,10 %and percentage of COD removal by 82,43%. Slurry produces unqualified TSS and COD with the standard quality of liquid waste. The economic potential of sugar palm leather waste and water for producing biogas is beneficial.